2015
DOI: 10.1111/gcb.12964
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation shift from deciduous to evergreen dwarf shrubs in response to selective herbivory offsets carbon losses: evidence from 19 years of warming and simulated herbivory in the subarctic tundra

Abstract: Selective herbivory of palatable plant species provides a competitive advantage for unpalatable plant species, which often have slow growth rates and produce slowly decomposable litter. We hypothesized that through a shift in the vegetation community from palatable, deciduous dwarf shrubs to unpalatable, evergreen dwarf shrubs, selective herbivory may counteract the increased shrub abundance that is otherwise found in tundra ecosystems, in turn interacting with the responses of ecosystem carbon (C) stocks and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 85 publications
4
45
2
Order By: Relevance
“…Other field studies found negative impacts of herbivory on the growth and morphology of an Arctic willow ( Salix glauca ) (Den Herder et al ., ) and other deciduous shrubs (e.g., Ylänne et al . , Olofsson et al ., ). Our results confirm that herbivores moderate the expansion of fast‐growing deciduous shrubs at local scales based on new and published data synthesized across the arctic ecosystems (Christie et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Other field studies found negative impacts of herbivory on the growth and morphology of an Arctic willow ( Salix glauca ) (Den Herder et al ., ) and other deciduous shrubs (e.g., Ylänne et al . , Olofsson et al ., ). Our results confirm that herbivores moderate the expansion of fast‐growing deciduous shrubs at local scales based on new and published data synthesized across the arctic ecosystems (Christie et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…), it is conceivable that, under moderate grazing pressure, less palatable evergreens could be given a competitive advantage despite their semi‐prostrate growth form (Christie et al . ; Ylänne, Stark & Tolvanen ). In our study, however, the advancement of evergreen dwarf shrubs in both ambient plots and exclosures suggests that this was not a result of altered competitive interactions between shrub species due to a release from grazing.…”
Section: Discussionmentioning
confidence: 99%
“…There could be several possible reasons for the observed expansion of evergreens. Though tall deciduous shrubs, such as B. nana, have been shown to be among the most responsive tundra species to increasing temperatures and have often been found to increase at the expense of evergreen shrubs (Chapin et al 1995;Bret-Harte et al 2001), it is conceivable that, under moderate grazing pressure, less palatable evergreens could be given a competitive advantage despite their semi-prostrate growth form (Christie et al 2015;Yl€ anne, Stark & Tolvanen 2015). In our study, however, the advancement of evergreen dwarf shrubs in both ambient plots and exclosures suggests that this was not a result of altered competitive interactions between shrub species due to a release from grazing.…”
Section: Discussionmentioning
confidence: 99%
“…Because NEE and GPP are closely tied to leaf area (Shaver et al, 2013), our results are broadly consistent with these studies suggesting early grazing diminishes overall production in the system. The largest effect of grazers on C uptake is removal of photosynthetic tissue although the impact of grazing on plant functional group composition can also be substantial (Cahoon et al, 2012;Metcalfe & Olofsson, 2015;Post & Pedersen, 2008;Ylänne, Stark, & Tolvanen, 2015). High-intensity grazing by geese also suppressed NEE and GPP compared to lower intensity or grazing removal from a wet tundra system (Sjögersten et al, 2008).…”
Section: Differences In Co 2 Exchange Among Experimental Treatmentsmentioning
confidence: 99%